PENERAPAN MODEL DISCOVERY LEARNING DALAM MENINGKATKAN AKTIVITAS BELAJAR TEMA 7 KELAS 1 SDN 1 SRIKATON - Najiyah, Husnun (CV Sintesia, 2024)
The problem in this research is the lack of students learning activity of the 7th grade students of SDN 1 Srikaton, Seputih Surabaya District, Central Lampung Regency. The purpose of this study is to increase student learning activities by applying the Discovery Learning model. The type of research used is classroom action research which consists of three cycles. Each cycle consists of stages of planning, implementing actions, observing, and reflecting. The data collection used an instrument of observing student and teacher activities which contained 18 indicators of success. The results showed that in the first cycle there were still 6 indicators of student success that had not been seen. In the second cycle there has been an increase but there are still 3 indicators of success that have not been seen. In the third cycle, all indicators of success have been seen, it is proven that most of the students have implemented 18 indicators of success.